2022
DOI: 10.1108/tqm-08-2022-0245
|View full text |Cite
|
Sign up to set email alerts
|

Critical challenges of integrating OPEX strategies with I4.0 technologies in manufacturing SMEs: a few pieces of evidence from developing economies

Abstract: PurposeThe study proposes to determine the impending challenges to lean integration with Industry 4.0 (I4.0) in manufacturing that aims at achieving desired operational performance. Integrating lean and Industry 4.0 as the two industrial approaches is synergetic in providing operational benefits such as increasing flexibility, improving productivity, reducing cost, reducing delivery time, improving quality and value stream mapping (VSM). There is an urgent need to understand the integrated potential of OPEX st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 160 publications
0
10
1
Order By: Relevance
“…They can revolutionize work on information management and integration among S.C. partners. Thus, they can enhance the performance, along with I4TE, in contrast to the previous research by Kiel et al [113], Delongate et al [114], and van de Wetering [115], which claimed the negative influence of I4TE on the performance and enhancement concerning environmental problems. This research is the first attempt to look at DSC from the information processing perspective, which has significant implications for DSC research in general.…”
Section: Theoretical Contributionscontrasting
confidence: 68%
“…They can revolutionize work on information management and integration among S.C. partners. Thus, they can enhance the performance, along with I4TE, in contrast to the previous research by Kiel et al [113], Delongate et al [114], and van de Wetering [115], which claimed the negative influence of I4TE on the performance and enhancement concerning environmental problems. This research is the first attempt to look at DSC from the information processing perspective, which has significant implications for DSC research in general.…”
Section: Theoretical Contributionscontrasting
confidence: 68%
“…In developing countries, a lack of adoption within an SME appears to be due to fear of job loss (Joshi et al, 2022). Therefore, Joshi et al (2022) encourage support at all levels of management, specifically towards the workers' development, involvement, and engagement.…”
Section: Developed and Developing Countries Represented In The Primar...mentioning
confidence: 99%
“…Departmental interaction -We find that this interaction is only mentioned in the literature from developing countries. Joshi et al (2022) highlight the importance of a supportive learning environment in SMEs in India, where learnings are captured and shared between departments, ensuring an understanding of how their work affects the rest of the organization. Also in India, Mittal et al (2020) found that input was sought from different departments such as sales, design, and production when a particular technology was being designed in their selected manufacturing SMEs.…”
Section: Developed and Developing Countries Represented In The Primar...mentioning
confidence: 99%
See 1 more Smart Citation
“…With the help of MCDM, which offers a well-structured framework for decision-making, factors based on adaptability, sustainability, and resilience are evaluated. In order to ensure the sustainability of Kaizen principles, the study aims to comprehend how the textile industry can adapt and flourish in the face of disruptions.Recent research has utilized MCDM and Structuring modeling to model critical success factors(Citybabu & Yamini, 2022;Joshi et al, 2022). ISM allows for understanding direct and indirect relationships among variables affecting the system under consideration, integrating elements measured on ordinal scales(Khaba et al, 2020).…”
mentioning
confidence: 99%